Sistem Pendukung Keputusan Pemilihan Tanaman Hias Hoya Carnosa Berbasis Android Menggunakan Metode TOPSIS - Fistiana, Fera Anggraini; Evanita, E; Riadi, Aditya Akbar (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2021)
Along with the rapid development of the times, the number of consumers who need ornamental plants provides good prospects for the future of the ornamental plant business, especially for ornamental plant farmers. Ornamental plants are not limited to ornamental plants that live in pots, but also include cut flowers, cacti, bonsai, hoya carnosa hydroponic plants and tabor flowers. This study aims to develop a Decision Support System (DSS) for the selection of hoya carnosa ornamental plants. The criteria for selecting hoya carnosa ornamental plants are to have a beautiful basic shape, come from long-lived plants, easy-to-form stems and branches, attractive and curvy skin surface, small leaves and quite dense, the condition of the plant is old enough and the plant is strong to form. The system was built using the Android programming language and applied the TOPSIS method to determine the hoya carnosa ornamental plants.